PENGARUH REWARD, PUNISHMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. MANUFAKTUR JAYA BALI - Adhi Krisna Yuliawan; Putu Pradiva Putra Salain (Universitas Triatma Mulya, 2023)
Jaya Bali Manufacturing company is one of the companies in the field of producing wood-based handicrafts in Bali. This company implements a target-oriented system, so that employees are required to be active in order to win the market. Employees are assets and capital for the company for the short and long term, so it is important for companies to be able to maintain and maintain a quality workforce. A fair reward system that guarantees the welfare of the entire workforce is a way that must be considered and carried out by the company. In awarding PT. Jaya Bali Manufacturing has not given rewards evenly. Such as rewards in the form of financial, namely the inappropriateness of bonuses received by some employees who can achieve the target. The number of samples taken as many as 96 employees, with the census method in which all employees are used as respondents. Based on the test results using regression analysis and t test, it is known that reward has a positive and significant effect on employee performance. This result means that if the reward given is higher, the employee's performance will also increase. Based on this, the hypothesis that the reward has a positive and significant effect on employee performance can be accepted, punishment has a positive and significant effect on employee performance. This result means that if the employee punishment is high, the employee's performance will also increase. Based on this, the hypothesis that punishment has a positive and significant effect on employee performance can be accepted and the last organizational culture has a positive and significant effect on employee performance. This result means that if the organizational culture in the company is good, then employee performance will increase.